Repensar el periodismo. Metadiscurso y concomitancias - Haber Guerra, YAMILE (Estudios sobre el Mensaje Periodístico, 2007)
The newsworthiness of an event does not depend only on the event itself, but on what the journalist and the reader themselves may contribute thanks to words ontological possibilities. On the one hand is the actual journalistic text, on the other is its meaning and interpretation; on the one hand is the event of note, on the other is the event’s image that is delivered to us by the language. Nowadays, the journalistic discourse issue goes beyond the news classic ‘what?’, ‘who?’, ‘when?’, ‘where?’, ‘why?’ and ‘what for?’ in order to attempt to answer: ‘(of) whom (is) and (to) whom (is)?’; ‘since when and until when?’; ‘from where and up to where?’